PROPORTION OF LEGALLY SIZE BLUE SWIMMING CRABS CAUGHT BY FISHERMEN IN BETAHWALANG VILLAGE - Azkia, Lana Izzul; Reza, Muhammad; Putri, Septi Malidda Eka (Jurusan Akuakultur, Universitas Bangka Belitung, 2022)
Blue swimming crab is a fishery product with high economic value in Indonesia. Betahwalang Village, Demak, is one of the crab fisheries locations in the province of Central Java. High selling prices and processing industry demand encourages fishing activities. One issue brought on by increased fishing activity is the smaller crab size. It will impact the crab fishing industry in Betahwalang. The majority of the fisherman in Betahwalang Village catch crabs using arad nets, simple gill nets, and traps. This study aims to evaluate the size of crab catch results on fishing gear used by fishermen and recommend proper fishing gear for catching crabs. This research was conducted in April 2019. The catch size of crab was the primary data collected for this study, also with data on fishing grounds, methods, and characteristics of fishing gear. Data were collected by observation, interviews, and measurements of fishing gear and the carapace width of the crab. The results of data collection and processing were analyzed descriptively. The results showed that the highest proportion of legal size crabs (carapace width ≥10 cm) was caught in traps, while the proportion of unlegal size crabs caught was mostly in bottom gillnets and mini trawl.